PENGARUH KEPUASAN KONSUMEN TERHADAP LOYALITAS MEREK (STUDI PADA PENGGUNA PONSEL BLACKBERRY DI KOTA TERNATE) - Laela Laela (Jurnal Manajemen Sinergi, 2013)
the aim of research to detect the influence of consumer satisfaction toward brand loyalty (study of Blackberry user ini Central of Ternate). Technique to sample removal which using in this research is judgement sampling with 100 respondents. This research utilize simple linier regression analysis, result shown that consumer satisfaction variable has significant influence toward brand loyalty in central of Ternate. Afterwards of hypotseis verivication pass trought T test (partial) known that H0 rejected and Ha accepted. Meaningful customer satisfaction influential toward brand loyalty of Blackberry user ini central Ternate.